2005
DOI: 10.1176/appi.ps.56.9.1115
|View full text |Cite
|
Sign up to set email alerts
|

Special Section on Seclusion and Restraint: Pennsylvania State Hospital System's Seclusion and Restraint Reduction Program

Abstract: Many factors contributed to the success of this effort, including advocacy efforts, state policy change, improved patient-staff ratios, response teams, and second-generation antipsychotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
1
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(159 citation statements)
references
References 29 publications
4
148
1
6
Order By: Relevance
“…Structured response teams, such as PERT, ensured fidelity to state polices and safe responses to psychiatric crises by placing the most experienced staff available at the scene of a crisis (3,24,25). In 2004, a statewide committee was formed to assess this staff training curriculum.…”
Section: System Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Structured response teams, such as PERT, ensured fidelity to state polices and safe responses to psychiatric crises by placing the most experienced staff available at the scene of a crisis (3,24,25). In 2004, a statewide committee was formed to assess this staff training curriculum.…”
Section: System Changesmentioning
confidence: 99%
“…Among these efforts is the Pennsylvania State Hospital Seclusion and Restraint Reduction Program. The program cited the effectiveness of response teams, staff training, data transparency, treatment malls, leadership, and advocacy in helping the hospitals reduce the use of containment measures (3). In addition, the National Association of State Mental Health Program Directors (NASMHPD) issued Six Core Strategies for Reducing Seclusion and Restraint Use (4).…”
mentioning
confidence: 99%
“…Three studies described staffing levels in terms of the ratio of staff to patients. In one, a decrease in hospital beds over a decade was accompanied by an increase in staff numbers (30). Two studies from the same state psychiatric hospital found statistically significant correlations between higher staffpatient ratios and lower use of seclusion and restraint (15,18).…”
Section: Staffingmentioning
confidence: 99%
“…Des traitements médicamenteux, par leur effet sur l'agitation et l'hostilité, ont montré qu'ils peuvent également contribuer à réduire l'utilisation de l'isolement ou d'autres mesures de contrainte [17,18]. Mais le problème demeure de la prise volontaire d'un médicament ou son administration sans le consentement du patient.…”
Section: Les Mesures Alternativesunclassified
“…Cependant, un grand nombre d'études descriptives et empiriques montrent, par un lien de causalité implicite, l'efficacité de différents types d'interventions sur la réduction des taux d'isolement [22]. Issus des réflexions de cliniciens mais aussi de pressions au niveau politique ou associatif, des programmes sont développés pour diminuer l'usage de la contrainte et de l'isolement [18,23,24], dont certains visent explicitement à les éli -miner. Ces initiatives alimentent la polémique et la controverse parmi les professionnels, comme l'illustre l'échange de lettres paru sur le site Psychiatric Services [25].…”
Section: Des Acquis Et Des Incertitudesunclassified